2003
DOI: 10.1063/1.1556183
|View full text |Cite
|
Sign up to set email alerts
|

Liquid metals as electrodes in polymer light emitting diodes

Abstract: We demonstrate that liquid metals can be used as cathodes in light emitting diodes ͑pLEDs͒. The main difference between the use of liquid cathodes and evaporated cathodes is the sharpness of the metal-polymer interface. Liquid metal cathodes result in significantly sharper metal-organic interfaces than vapor deposited cathodes, due to the high surface energy of the metals. The sharper interface in pLEDs with liquid metal cathodes is observed by neutral impact collision ion scattering spectroscopy and low energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 35 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…No non surface‐active impurities were found in reference . Such impurities could have been be detected at a concentration greater than about 0.1 atom% based on reference where chlorine could clearly be identified as an impurity within the polymer poly(p‐phenylenvinylen) (PPV) at a concentration of about 0.1 atom%.…”
Section: Surface Spectroscopy Vs Thermodynamic Conceptsmentioning
confidence: 99%
“…No non surface‐active impurities were found in reference . Such impurities could have been be detected at a concentration greater than about 0.1 atom% based on reference where chlorine could clearly be identified as an impurity within the polymer poly(p‐phenylenvinylen) (PPV) at a concentration of about 0.1 atom%.…”
Section: Surface Spectroscopy Vs Thermodynamic Conceptsmentioning
confidence: 99%
“…10 With respect to the Al-DPBT-ITO cell case, measurements were performed at a more moderate vacuum of 40 mbars to avoid Hg evaporation. Also in this case the cell shows a voltage driven conductance switching behavior, as shown in Fig.…”
mentioning
confidence: 99%
“…However, it was suggested 7 that the interface stability does play an important role in PLED degradation. Diffusion of metals into PPV derivatives and PPV model systems during deposition has been observed, [8][9][10][11][12] but the dynamics of the diffusion process was not investigated. Furthermore, it has been shown that PLEDs with barium cathodes have better efficiencies and longer lifetimes than devices with calcium cathodes.…”
Section: Introductionmentioning
confidence: 99%